2020
DOI: 10.3389/fonc.2019.01556
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Complexity of the Tumor Microenvironment in K-ras Mutant Lung Cancer: Finding an Alternative Path to Prevention and Treatment

Abstract: Kirsten rat sarcoma viral oncogene (K-ras) is a well-documented, frequently mutated gene in lung cancer. Since K-ras regulates numerous signaling pathways related to cell survival and proliferation, mutations in this gene are powerful drivers of tumorigenesis and confer prodigious survival advantages to developing tumors. These malignant cells dramatically alter their local tissue environment and in the process recruit a powerful ally: inflammation. Inflammation in the context of the tumor microenvironment can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 238 publications
0
24
0
Order By: Relevance
“… 7 Some studies have shown that chronic inflammation or wound-healing process in abnormal microenvironment activates oncogenic signaling and promotes tumorigenesis. 8 11
Fig. 1 The updated landscape of tumor microenvironment (TME).
…”
Section: Persistent Updating Concept Of Tmementioning
confidence: 99%
“… 7 Some studies have shown that chronic inflammation or wound-healing process in abnormal microenvironment activates oncogenic signaling and promotes tumorigenesis. 8 11
Fig. 1 The updated landscape of tumor microenvironment (TME).
…”
Section: Persistent Updating Concept Of Tmementioning
confidence: 99%
“…A COPD-like inflammation supported a tumourigenic effect of KRAS mutant lung cancer, driven by HIF-1α [ 302 , 303 ]. Additionally, KRAS mutant NSCLC secreted a specific cytokine profile with neutrophil recruitment into the tumour micro-environment, resulting in a pro-hypoxic condition [ 304 ]. HIF-1α inhibition (by Ras-PI3K-Akt pathway downregulation) in cell line models harbouring KRAS mutation repressed metastatic behaviour (proliferative and metastatic properties) [ 305 ].…”
Section: Prognostic Implications Of Hypoxia In Lung Cancermentioning
confidence: 99%
“…On the other hand, the T cell-mediated anti-tumoral response was decreased later in carcinogenesis progression (30 weeks of age) and was accompanied by a significant increase in type-2 polarized macrophages ( Figure 1 e, lower panels). This immune phenotype of the K-Ras G12D lungs mirrors the setting of human advanced NSCLC, for which the spontaneous conversion from an anti-tumorigenic to a pro-tumorigenic microenvironment has been described to occur over time [ 80 , 81 , 82 ]. Moreover, PD-L1 was detectable by means of IHC in all samples tested (data not shown), with a percentage of positive tumor cells ranging from 15% to 40%, similar to what was observed in most human NSCLC [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of these results, we can state that anti-ROS1 DNA electrovaccination has the potential to impair NSCLC progression, even if it is not able to completely block lung carcinogenesis. However, it is important to note that, as in human NSCLC, constitutively active K-Ras expression also induces an immunosuppressive tumor microenvironment [82], which may contribute to the limited effectiveness of our vaccines, in these murine K-Ras G12D models. In particular, we have observed the recruitment of CD8 + T cells and M1-type macrophages in the lungs of K-Ras G12D mice in the early stages (10 weeks of age) of NSCLC progression, which hints at the existence of a spontaneous anti-tumor immune response.…”
Section: Discussionmentioning
confidence: 99%